Syndemic conditions associated with increased HIV risk in a global sample of men who have sex with men. (15th January 2014) - Santos, Glenn-Milo; Do, Tri; Beck, Jack; Makofane, Keletso; Arreola, Sonya; Pyun, Thomas; Hebert, Pato; Wilson, Patrick A; Ayala, George
Abstract : Objective: We evaluated the relationship among syndemic conditions (defined as a cluster of interconnected psychosocial health conditions), sexual behaviours and self-reported HIV infection in a global sample of men who have sex with men (MSM). Methods: We used generalised estimating equations logistic regression models with robust SEs to assess the relationships among cumulative number of syndemic conditions—including depression, substance use, violence, sexual stigma and homelessness—and unprotected anal intercourse (UAI) and HIV infection, while accounting for clustering within-country in a global cross-sectional survey of 3934 MSM across 151 countries. Results: We observed parallel, significant dose–response associations between the number of syndemic conditions and UAI, as well as number of syndemic conditions and HIV infection. Compared with participants without syndemics, the adjusted OR (aOR) for UAI among those with 1, 2 and 3 or more syndemic conditions were 1.44 (Bonferroni-adjusted 95% CI 1.23 to 1.68), 1.89 (1.51 to 2.36) and 2.03 (1.43 to 2.89), respectively. Compared with participants without syndemics, the aOR for HIV infection among those with 1, 2 and 3 or more syndemic conditions were 1.67 (1.24 to 2.26), 2.02 (1.44 to 2.85) and 2.35 (1.31 to 4.21), respectively. Conclusions: This analysis provides evidence of intertwining syndemics that may operate synergistically to increase HIV risk among MSM globally. To curb HIV effectively and advance the health of MSM, multiple conditions must be addressed concurrently using multi-level approaches that target both individual and structural risk factors.